ANALISIS KESALAHAN SISWA PADA MATERI FUNGSI BERDASARKAN KRITERIA WATSON - Anisa Nurul Islami; Andini Nugrahaeni; Siti Rahmayani; Luvy Sylviana Zanthy (IKIP Siliwangi, 2021)
This research was conducted with the aim of even more types of student errors in learning. The method used in this research is descriptive qualitative with the research subjects are 10 students from SMA Negeri 1 Gununghalu. Error analysis data solving functional matter problems were obtained from written tests and interviews. Data processing in this study using Microsoft Excel. The result showed that, the level of understanding of students' mathematical concepts was low. This is known by the function material which show that the errors that are often made by students according to Watson’s criteria are missing data error and skill problem solving operations are lost and there are still students who cannot translate the questions into mathematical model and steps. Early in the work on the problem. In addition, students are also less thorough and do not understand the questions so that students do not get data or information which results in incomplete problem solving.